1995
DOI: 10.1177/0032855595075001002
|View full text |Cite
|
Sign up to set email alerts
|

A Content Assessment and Comparative Analysis of Prison-Based AIDS Education Programs for Inmates

Abstract: Although it is true that inmates in U.S. prisons are experiencing high rates of HIV disease, it also is true that incarceration affords a meaningful opportunity to prevent the spread of HIV/AIDS through education. Consequently, providing effective education programs for inmates is an important corrections and public health concern. In an attempt to assess our current efforts in this area, a survey of all 50 state departments of corrections was conducted. As part of that survey, descriptions of inmate AIDS educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Frequently addressed topics include smoking, alcohol and drug use, HIV and STD prevention, and violence prevention. 13,29,93,[132][133][134][135][136] Few jails or prisons have established comprehensive health education programs despite their ability to have ongoing contact with vulnerable populations.…”
Section: Roles Of Correctional Systems In Public Health In Urban Commmentioning
confidence: 99%
“…Frequently addressed topics include smoking, alcohol and drug use, HIV and STD prevention, and violence prevention. 13,29,93,[132][133][134][135][136] Few jails or prisons have established comprehensive health education programs despite their ability to have ongoing contact with vulnerable populations.…”
Section: Roles Of Correctional Systems In Public Health In Urban Commmentioning
confidence: 99%
“…Nearly all of the studies in this category were concerned with educational programs, whether led by peers or professionals; peer education was highlighted as particularly beneficial (Ayanwale, 2008; Boudin et al, 1999; Clark & Boudin, 1990; Collica, 2002, 2007; Martin, Zimmerman & Long, 1993; Lyons et al, 2014; Martin et al, 1995; Grinstead, Faigeles & Zack, 1997; Ross, 2006; Scott et al, 2004; West & Martin, 2000). Education programs were found to be effective in informing incarcerated men and women about HIV transmission and risk behaviors, and changing attitudes and beliefs (Ayanwale et al, 2008; Boudin et al, 1999; Grinstead, Faigeles, & Zack, 1997; Ross et al, 2006; Scott et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…These interventions had positive effects on a variety of key outcomes including HIV knowledge, intentions to change risky behaviors, perceived risk of infection, coping and social support, and HIV test rates (Ayanwale et al, 2008; Boudin et al, 1999; Bryan et al, 2006; Collica, 2007; Grinstead et al, 1997; Lyons et al, 2014; Martin et al, 1993; Martin et al, 1995; Ross et al, 2006; Scott et al, 2004; St Lawrence et al, 1997; West & Martin, 2000; West, 2001). One evaluation of a risk reduction program for women inmates suggested that communication skills were just as important to reducing HIV risk as knowledge of HIV and safe sex, as women with these skills were better able to negotiate with sex partners (St Lawrence et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…the comprehensiveness of the programme (including whether it includes safer drug use and safer sex information and demonstrations about how a condom is properly used, or how drug paraphernalia can be safely cleaned); . whether it is linguistically and culturally appropriate (Martin et al, 1995); . whether it is specific to the needs of various populations, in particular female prisoners and youth (Martin et al, 1995); .…”
Section: Hiv/aids Educationmentioning
confidence: 99%